Kemanfaatan Perpustakaan dalam Pembelajaran dan Penelitian Mahasiswa IPB serta Strategi Peningkatannya - Janti G. Sujana; Deden Himawan (Perpustakaan IPB, 2020)
Facing the disruptive era IPB Library needs to anticipate various changes by conducting self-evaluation through assessing the impact of their existence for students. Therefore, this study aims: (1) Knowing the relationship between the frequency of student visits to the IPB Library and the GPA; (2) Knowing the relationship between the number of IPB library books borrowed by students and the GPA; (3) Knowing the benefits of the IPB Library in supporting student learning and research processes; (4) Knowing the role of IPB librarians in supporting the learning and research processes of their students; (5) Formulate strategies for the IPB Library to increase its benefits for the learning and research processes of its students. This research is a quantitative study, using a correlation test to see the relationship between the frequency of student visits to the IPB Library and the number of the IPB Library books borrowed by the students with the GPA. This study also used a survey method with a questionnaire accompanied by interviews with three IPB lecturers. The results showed that there was no correlation between the frequency of student visits to the library and the number of library books borrowed on the student's GPA. However, students' perceptions regarding the support of the IPB Library on their learning and research are very good, the average percentage of respondents who agree on the benefits of the library in their learning and research processes is above 90%. Respondents' perception of librarian support in helping students learn is very good, but librarian support for student research is considered lacking. Strategies to increase the benefits of the library and librarians on student learning and research process need to be adjusted to the behavior of the millennial generation. Therefore, it is recommended that the IPB Library immediately implement the concepts based on industrial revolution 4.0. IPB librarians should be improved their competence related to information literacy skills and mastery of information and communication technology.